WASTE-WATER TREATMENT BY ELECTRO-OXIDATION PROCESS WITH TiO2 - Ghanim, Fanar; Abdullah, Thamer Adnan (Journal of Advanced Manufacturing Technology (JAMT), 2016)
The environment of wastewater containing toxic organic compounds by the industrial community has been increased significantly in the recent past. So the treatment of such wastes generated from the industries is considered necessary as well as important in every aspect. Untreated wastewater if allowed to accumulate, the decomposition of organic material leads to the production of toxic gases. For wastewater, the objective is to remove or reduce the concentration of organic and inorganic compounds. Some of the constituents and compounds present in wastewater lead to serious problem to the environment. This study presents the treatment of petroleum wastewater using nanoscale TiO2 in the presence of electro-oxidation process. TiO2 physio-chemical characterization of were analyzed using UV, SEM with EDX, XRD and FTIR. The influence of TiO2 dosage and initial pH on % COD reduction was studied. The results indicate that using TiO2 in combination with electrocoagulation is an efficient method for the treatment of petroleum wastewater a dosage of 0.15 g/l and a pH 10 in CD 9.